PENERAPAN TERAPI BERMAIN ORIGAMI PADA AN. M USIA PRA SEKOLAH (5 TAHUN) UNTUK MENGURANGI KECEMASAN AKIBAT HOSPITALISASI PADA PENYAKIT TYPHOID DI RUANG MELATI RUMAH SAKIT TK.II DUSTIRA CIMAHI 15- 16 MEI 2023 - Septia, Widi; Zulva, Siti (Yayasan Putra Sukamanah Sejahtera, 2024)
Typhoid Febrile disease caused by salmonella typhi bacterial infection that spreads throughout the body is known as typhoid fever (TF). Most children with typhus require hospitalization for the recovery phase, which can sometimes cause problems for the child's psyche. WHO said in 2018 the incidence in Indonesia was 81% per 100,000 population experiencing typhoid fever. Hospital childcare requires that children be separated from comfortable, caring, and fun environments, such as their home, games, and playmates, while doing pediatric care in the hospital results in the child experiencing anxiety. Anxiety is a normal human state that feels threatened that includes cognitive, affective, and behavioral responses. One way that can be done to reduce anxiety in children is origami play therapy. Origami is one of the unique crafts that can be fun and serve as educational entertainment, especially for children. This study aims to apply origami play therapy nursing care to preschool children (3-6 years) to reduce anxiety due to hospitalization in typhoid disease in the Jasmine Room of TK.II Dustira Cimahi Hospital. The case study design used is a case study with a descriptive approach. The subjects in this case study were preschool-aged children (3-6 years) before play therapy A5 (mild weight) patient anxiety scale after therapy became A1 (light) according to Vfas. It can be concluded that origami play therapy can reduce anxiety in children with typhoid fever. It is hoped that origami play therapy can provide information in overcoming anxiety in preschool-aged children with typhoid fever.